2012
DOI: 10.1080/02640414.2012.661070
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness of primary school children in relation to overweight prevalence and physical activity habits

Abstract: A cross-sectional study was carried out to analyse, through a limited number of fitness tests, the main conditioning and coordinative abilities in children aged 8-9 years, and their relationship with gender, anthropometric variables and physical activity habits. The height and weight of 256 boys and 241 girls were measured and information about physical activity habits was collected using a self-administered questionnaire. Physical performance was assessed by means of a few standardised tests: 'sit & reach', m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
64
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 22 publications
16
64
0
4
Order By: Relevance
“…Moreover, there is a clear association between children's performance and BMI, also confirmed by other related studies (15, 19, 24). With the exception of the medicine ball-throw in which high BMI resulted in better performance in upper body explosive strength (presumably due to the confounding muscle and fat in BMI), in all remaining physical tests, BMI revealed a clear negative correlation with performance.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, there is a clear association between children's performance and BMI, also confirmed by other related studies (15, 19, 24). With the exception of the medicine ball-throw in which high BMI resulted in better performance in upper body explosive strength (presumably due to the confounding muscle and fat in BMI), in all remaining physical tests, BMI revealed a clear negative correlation with performance.…”
Section: Discussionsupporting
confidence: 86%
“…This is in agreement with studies considering older children and adolescents which have suggested a non-linear relationship between BMI and health related fitness (Huang & Malina, 2007; Mak et al., 2010). Studies have indicated that over-nutrition may affect the physical fitness of children, with overweight and obese children performing more poorly on physical fitness tests then normal weight children, when required to move their bodyweight through space (Brunet et al., 2007; Ceschia et al., 2016; Dumith et al., 2010; Prista et al., 2003; Raudsepp & JĂŒrimĂ€e, 1996; Sacchetti et al., 2012; Shang et al., 2010; Tokmakidis et al., 2006; Truter et al., 2010). Walking and running at the same speed requires a greater absolute energy expenditure in obese children when compared to normal weight children (Maffels et al., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A baixa aptidĂŁo fĂ­sica estĂĄ associada a elevados Ă­ndices de colesterol e triglicerĂ­deos, pressĂŁo arterial e risco maior a obesidade, o que pode ser influenciado pelo estado socioeconĂŽmico, bem como por outros fatores, tanto ambientais, disponibilidade de espaços para realizar atividades, quanto sociais, influĂȘncia dos amigos e pessoas prĂłximas no comportamento relacionado Ă  prĂĄtica de atividade fĂ­sica 30 . Quanto Ă  Agilidade e Velocidade, nas idades de 7 a 10 anos os gĂȘneros nĂŁo apresentaram diferenças significativas, resultado semelhante sĂŁo encontrados com estudo realizado em crianças Sul-Africanas de 8 e 9 anos 31 , porĂ©m difere de um estudo que encontrou resultados estatisticamente significantes de um melhor desempenho dos meninos 32 . Estas valĂȘncias sĂŁo essenciais nas tarefas do dia-a-dia, como andar desviando de pessoas ou obstĂĄculos, locomover-se carregando objetos ou deslocar-se rapidamente 36 .…”
Section: Discussionunclassified